Udayana School of Kajian Budaya compared to the Spell of British Cultural Studies: Critical Discourses in Debate - A A Ngurah Anom Kumbara; Mayske Rinny Liando; Ida Bagus Gde Putra; Nanang Sutrisno (Jurnal Kajian Bali (Journal of Bali Studies), 2024)
This article attempts to look deeper into the Udayana School of Kajian Budaya compared to the spell of British Cultural Studies to understand both modes and critical discourses in debate. It hopes to widen the horizon on the plurality of cultural studies versions existing beyond Britain, the United States and Europe; specifically the Udayana School of Kajian Budaya in Bali and broadly in Indonesia. Hence, the authors conducted a literature search to compile relevant publications, interviewed Kajian Budaya lecturers and alumni, and employed critical interpretive analysis to the data. The study indicates formation of the British and the Udayana School variants were influenced by critical theory of the Frankfurt School and postmodernism ideas of French and American thinkers, which critiqued institutions of modernity, capitalist society, positivism in scientific inquiry, ‘classical’ enlightenment thought, and the culture industry. However, the Udayana School of Kajian Budaya exhibits distinctiveness in its study areas, approach and paradigm.